The Impacts of Overinvestment and Financial Constraints on Seasoned Equity Offering Long-Run Performance - Lu, Pei-shan; Young, Weiju; Hsieh, Meng Sung (International Journal of Economics and Financial Issues, 2017)
This study considers overinvestment and financial constraints as factors that associate with managerial incentives of firms conducting seasoned equity offerings (SEOs). The results show that pre-issue overinvestment and financial slack are negatively related to the long-run performance of SEO firms. It implies that SEOs of firms with these two characteristics are driven by managerial incentive misalignment, resulting in their lackluster long-run performance after SEOs. In other words, overinvesting and financially unconstrained firms may conduct SEOs due to managers' empire-building desires. These results should remind the board of directors to prevent managers' equity financing from serious overinvestment and that long-run investors should avoid buying new-issue shares of firms with overinvestment and financial slack. Keywords: Seasoned Equity Offerings (SEOs); Overinvestment; Financial Constraints; Managerial Incentives JEL Classifications: G30, G32